Management of Zakat Funds for Education Sharia Economic Law Perspective - Sayyid Ridha; Imron Rosyadi; Mr. Anat Maisu; Alberto Emmanuel Conti Morales; Muthoifin (Demak Universal Journal of Islam and Sharia, 2024)
This study aims to analyze the picture and understanding of the management of zakat funds for education at the Dompet Dhuafa zakat institution, as well as what is given in Sharia economic law. Which management of zakat funds can be for education, and can be realized in the form of education care programs by providing education costs to students who come from poor families. The research method used is qualitative with a descriptive approach through interviews and observations. The results showed that five fund management procedures are implemented by the school, as stipulated by the Dompet Dhuafa Foundation: financial planning, receipt of funds, expenditure of funds, accountability of funds, and financial control. The distribution of zakat funds for education by Dompet Dhuafa is included in productive zakat given directly to mustahik, namely schools, as a real investment that is considered right on target.